ANALISIS EFEKTIVITAS DAN EFISIENSI DISTRIBUSI BERAS MISKIN ( RASKIN ) DI DESA TOLONGANO KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Rifal, Rifal; Sulaeman, Sulaeman (AGROTEKBIS, 2016)
Rice for the poor program (Raskin) is one of the Indonesian governments program to increase the consumption of poor households (RTM) and reducing the burden of Target Households spending through the partial fulfillment of rice food needs. The purpose of this study was to analyze the effectiveness and efficiency programs in the RaskinTolongano Village, District of South Banawa, Donggala. This research was conducted in the village of Tolongano in October until Novebmber 2015. The data used in this research is data Primary and secondary. Analysis of the data used in this research is the method of qualitative (descriptive) and quantitative. The results showed that the effectiveness of Raskin in the village Tolongano still relatively low at 40.00%. This indicates that the distribution of Raskin in the village Tolongano ineffective because Based on the analysis of the attitude of households targeted beneficiaries concluded that the distribution of Raskin in the village Tolongano not effective, because based on the attitude of the target households, indicators of the effectiveness of Raskin which meets just the right quality and on time, while for other indicators are not appropriately priced, targeted, and not just the right amount. Marketing efficiency in the village Tolongano is 0.07, indicating that the distribution of Raskin in the village Tolongano been efficient, since the calculation of the efficiency of distribution Raskin under one.Â Key Words: Distribution, effectiveness and efficiency, poor household, Raskin.